Character-loaded Children's Reading as a Builder of Pancasila Student Profiles - Kuntoro Kuntoro; Sudarmi Sudarmi (UM Purwokerto Press, 2023)
This study aims to determine the character value of children's reading in the Indonesian language book â€œI Canâ€ Class I Elementary School. It contains Pancasila Student Profiles in the Independent Curriculum. In this book there is a reading: Duk! Duk1, Be Careful1, Caca Can, Beware of Germs!, Animal Parade, Mimi Bravei, Kiki and Gaga, Bimo at the Market, Bayu Don't Know. Character is a form of personality or character of a person that comes from a collection of policies and is manifested through behavior that is in accordance with ethics/moral principles. Character is formed through a learning process in several places, such as at home, school, and in the neighborhood where they live. The method used in this research is content analysis method. Based on the results of research on children's reading there are several character values contained in the Pancasila Student Profile. Pancasila students are the embodiment of Indonesian students as lifelong students who have global competence and behave in accordance with Pancasila values, with six main characteristics: faith, fear of God Almighty, and noble character, global diversity, mutual cooperation, independence, critical reasoning, and creative Indonesian students are lifelong students who have global competence and behave according to Pancasila values.